Optimising the Spatial and Production Input Features to Improve Efficiency of Hill Farm Production Systems - Vittis, Yiorgos; Gadanakis, Yiorgos; Mortimer, Simon (Frontiers in Sustainable Food Systems, 2021)
Integration of crop and livestock production systems (ICLS) represents a method for enhancing the sustainability of agricultural systems. Introducing more diversified farm production plans increases profitability and resilience by minimising the negative environmental impacts of agricultural production. Examining farm businesses located in Less Favoured Areas (LFAs) of England, we investigate how conversion into more integrated systems impacts on profitability. Thus, providing knowledge that can enable structural changes on the farm level towards enhancing financial performance and the sustainable intensification of the production system. Through Linear Programming (LP), four distinct optimisation scenarios are estimated, demonstrating the different dynamics between more specialised and more integrated-diversified (intensified) production systems. Data regarding physical and financial performances of 139 farm businesses were derived from the Farm Business Survey (FBS) for the accounting year of 2013–2014. Our findings suggest that there is a lot of potential for increasing profitability of hill farms through optimisation of ICLS. Policy interventions may accommodate productivity challenges within the LFAs via the construction of networks of transferrable knowledge to enable farmers gain knowledge on benefits emerging from ICLS. Hence, promote strategies and risk mitigation practises that could allow hill farmers to develop a sustainably intensified production system that is maximising the production capacity of the available natural resources.